Jakie ciało nie osiągnie królestwa Bożego? - Szram, Mariusz (The Biblical Annals, 2019)
The aim of the article is to compare the exegesis of verse 1 Kor 15, 50 in early patristic literature on the example of the writings of three authors: Irenaeus of Lyon – representative of the Asian tradition; Tertullian of Cartage – associated with the North African tradition, similar in many points to Asian; and Origen – originating from the Alexandrian tradition. All these writers used the moral interpretation of the phrase “flesh and blood” as sinful deeds, which should be abandoned to enter the kingdom of heaven. Each of them, however, also allowed the literal explanation of this verse, trying to reconcile it with the truth of faith about the bodily resurrection. Irenaeus emphasized that the body can not be resurrected and reach the kingdom of God with its own strength, but only with the help of the Holy Spirit. Tertullian thought that the body in the earth would resurrect, but it would not be able to enter the kingdom of heaven without accepting features adapted to the new reality. Origen went the farthest, undermining the possibility of returning to earth-shaped bodies. The analysis of early Christian commentary on the Pauline verse proves that patristic exegesis was theologically oriented and depended on the contemporary doctrinal disputes. One may also notice a certain paradox: sometimes in order to justify a particular philosophical and theological stand, a proponent of literalism or moderate allegorisation might attach more importance to the portable meaning of the inspired text than the alleged allegorist, which in turn referred to a far-reaching literal interpretation.